American religions and the family : how faith traditions cope with modernization and democracy - Browning, Don S.; Clairmont, David A. (Columbia University Press, 2007)
"Religions respond to capitalism, democracy, industrialization, feminism, individualism, and the phenomenon of globalization in a variety of ways. Some religions conform to these challenges, if not capitulate to them; some critique or resist them, and some work to transform the modern societies they inhabit. In this unique collection of critical essays, scholars of Judaism, Christianity, Islam, Hinduism, Buddhism, Confucianism, and Native American thought explore the tension between modernization and the family, sexuality, and marriage traditions of major religions in America. Contributors examine how various belief systems have confronted changing attitudes regarding the meaning and purpose of sex, the definition of marriage, the responsibility of fathers, and the status of children. They also discuss how family law in America is beginning to acknowledge certain religious traditions and how comparative religious ethics can explain and evaluate diverse family customs. Studies concerning the impact of religious thought and behavior on American society have never been more timely or important. Recent global events cannot be fully understood without comprehending how belief systems function and the many ways they can be employed to the benefit and detriment of societies. Responding to this critical need, American Religions and the Family presents a comprehensive portrait of religious cultures in America and offers secular society a pathway for appreciating religious tradition"--Provided by publisher.